Tensile Properties of the Deep Transverse Metatarsal Ligament in Hallux Valgus: A CONSORT-Compliant Article. Issue 8 (February 2016) - Abdalbary, Sahar Ahmed; Elshaarawy, Ehab A.A.; Khalid, Bahaa E.A.
Abstract : Abstract: The deep transverse metatarsal ligament (DTML) connects the neighboring 2 metatarsal heads and is one of the stabilizers connecting the lateral sesamoid and second metatarsal head. In this study, we aimed to determine the tensile properties of the DTML in normal specimens and to compare these results with hallux valgus specimens. We hypothesized that the tensile properties of the DTML would be different between the 2 groups of specimens. The DTML in the first interspace was dissected from 12 fresh frozen human cadaveric specimens. Six cadavers had bilateral hallux valgus and the other 6 cadavers had normal feet. The initial length ( L 0 ) and cross-sectional area ( A 0 ) of the DTML were measured using a digital caliper, and tensile tests with load failure were performed using a material testing machine. There were significant between-groups differences in the initial length ( L 0 ) P  = 0.009 and cross-sectional area ( A 0 ) of the DTML P  = 0.007. There were also significant between-groups differences for maximum force (N) P  = 0.004, maximum distance (mm) P  = 0.005, maximum stress (N/mm 2 ) P  = 0.003, and maximum strain (%) P  = 0.006. The DTML is an anatomical structure for which the tensile properties differ in hallux valgus.